ОСОБЛИВОСТІ ПОПЕРЕДНЬОГО ВІДНОВЛЕННЯ ГОСПОДАРСЬКО ЦІННИХ ПОРІД ПІД НАМЕТОМ ПРИРОДНИХ ДУБОВИХ ЛІСОСТАНІВ В УМОВАХ СВІЖОЇ ТА ВОЛОГОЇ КЛЕНОВО-ЛИПОВОЇ СУДІБРОВИ ЛІСОСТЕПУ СУМЩИНИ - Rumіantsev, M. Н.; Lyk’yanets, V. A.; Samoday, V. P.; Ihnatenko, V. A.; Sotnikova, A. V.; Trophymenko, M. Ye. (Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM), 2018)
Introduction Natural stands of pedunculate oak (Quercus robur L.) in the Left-bank Forest-Steppe of Ukraine in the fairly fertile oak forest types grows on large areas (over 27 thousand hectares). In these conditions, mixed natural oak stands are formed in fresh and moist fairly fertile site types. According to Chernyavskiy (1989), after the seed year, the number of good self-seeding of oak under the forest canopy in fairly fertile sites varies from 26.4 to 33.9 thousand stems per ha, which is a significant reserve for the natural regeneration of oak stands. Materials and Methods During the study, the methodology of counting the natural reproduction, developed in URIFFM, was used as well as other generally accepted methods of forestry. Advance seedlings were divided by species, age, height and viability (good and unreliable) and its frequency of occurrence was determined. To identify the features of the advance growth, 150 registration sites were established on 6 sample plots. Results After a seed year in fresh fairly fertile sites under the canopy of natural oak stands, advance seedlings of economically valuable species appeared in a sufficient number of up to 18.7 thousand stems per ha. The numbers of advance oak seedlings in the plots varied over a wide range of 2.3–10.3 thousand stems per ha. The largest number of young oak seedlings, 9.9 thousand stems per ha, was registered under the canopy of the overmature coppice oak stand, where the share of oak in the composition reached 100 %, and the smallest one, 2.3 thousand stems per ha, in the oak forest, where the oak part was 70 %. The advance seedlings of pedunculate oak and Norway maple (Acer platanoides L.) were the most frequent in the conditions of moist maple-lime fairly fertile oak site type. The total number of reproduction was less than that in fresh fairly fertile oak sites, up to 16.0 stems per ha. The pedunculate oak reproduction ranged from 2.4 to 5.1 thousand stems per ha, and the share in the total reproduction was from 21 to 43 %. By age, sprouts dominated among the oak seedlings, accounting for 79–82 %. The proportion of 2–3-year-old oaks was 13–21 %, and 4–8-year-old from 4 to 7 %. Older advance reproduction was absent. In general, the quantitative and qualitative analysis of the advance reproduction of the main forest species, pedunculate oak, and its height and age structure indicate that in the conditions of fresh and moist fairly fertile oak sites in the Left-bank Forest-Steppe zone, the success of the regeneration is characterized as “insufficient” or “bad” according to the scale developed in URIFFM. Regeneration of associate and secondary species in all areas was “successful”. By the density, the reproduction was dense and very dense and only on some sites of medium density. Conclusions Advance regeneration in oak stands of different ages in fresh and moist maple-lime fairly fertile oak site types was generally unsatisfactory. However, in separate plots after the seed year under the canopy of old-aged natural oak stands, reliable oak seedlings of pedunculate oak were accounted in a sufficient quantity, more than 10 thousand stems per ha. This natural reproduction must be preserved by tending felling for regulating the cenotic relationship between the main, associate and secondary species as parts of the advance growth, in order to form a new generation of oak forests naturally by seeds. 3 Tables, 8 Refs.